Consumismo na pós-modernidade: uma questão de gênero? - Patrícia Fasolo Romani; Gustavo Espíndola Winck; Marlene Neves Strey (Ciências Sociais Unisinos)
This paper addresses a discussion on excessive consumption in postmodernity and its effects on female subjectivity. From a theoretical perspective guided by the social sciences and gender studies, consumerist behavior and its pathological bias are seen primarily as symptomatic products of sociocultural transformations, which impact the emotional lives of women.